Compassion Satisfaction, Burnout, and Secondary Traumatic Stress Among Critical Care Nurses in Iran. (January 2020) - Salimi, Sedigheh; Pakpour, Vahid; Rahmani, Azad; Wilson, Marian; Feizollahzadeh, Hossein
Introduction: This study investigated the relationship between compassion fatigue and compassion satisfaction among Iranian nurses working in critical care units.Method: A cross-sectional, descriptive survey using the Professional Quality of Life instrument was administered to 400 nurses working in the intensive care units of Iranian hospitals.Results: High risk levels of burnout and secondary traumatic stress existed among 42% and 96% of participants, respectively. Significant positive relationships were detected between burnout and secondary traumatic stress. An inverse relationship was detected between measures of compassion fatigue and compassion satisfaction.Discussion: To ensure culturally congruent care, it is important to evaluate professional quality of life within the context of specific cultures and societies. Iranian critical care nurses are at risk for burnout and secondary traumatic stress. Personal self-care and organizational wellness approaches that consider cultural norms should be designed to boost compassion satisfaction and reduce negative effects of stressful work environments.